1996
DOI: 10.1557/proc-420-239
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Transport Mechanisms in p+a-SiC:H/n c-Si Heterojunctions: dark J-V-T Characteristics

Abstract: In the present paper we show results of dark current-voltage measurements performed on p+ a- SiC:H/n c-Si heterojunction diodes at various temperatures (100–400K). We investigated the voltage derivative of these J-V curves in order to the distinguish possible current transport mechanisms. It was found that for low temperatures (<300K), the current is determined by recombination of carriers in the crystalline silicon, whereas at high temperature (>300 K), by a tunnelling mechanism. At room temperature, bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…However, this result contrasts with Magafas et al [6] who found diffusion-recombination (in the crystalline silicon) mechanisms in undoped a-SiC/p c-Si heterojunctions for applied voltages lower than 0.4 V and temperatures higher than 250 K. On the other hand, in p + a-SiC/n c-Si heterojunctions different transport mechanisms have been found, for instance thermal injection [4] and tunnelling [13] for temperatures higher than 300 K and low forward voltages (V < 0.6 V). Notice that these transport mechanisms are not observed in our samples throughout the range of measured temperatures and biases.…”
Section: Current-voltage Characteristicsmentioning
confidence: 60%
“…However, this result contrasts with Magafas et al [6] who found diffusion-recombination (in the crystalline silicon) mechanisms in undoped a-SiC/p c-Si heterojunctions for applied voltages lower than 0.4 V and temperatures higher than 250 K. On the other hand, in p + a-SiC/n c-Si heterojunctions different transport mechanisms have been found, for instance thermal injection [4] and tunnelling [13] for temperatures higher than 300 K and low forward voltages (V < 0.6 V). Notice that these transport mechanisms are not observed in our samples throughout the range of measured temperatures and biases.…”
Section: Current-voltage Characteristicsmentioning
confidence: 60%
“…van Cleef et al evaluated the current-voltage characteristics of the thin (10 nm) p þ a-SiC:H/n c-Si heterojunction at various temperatures (100 -400 K), and concluded that the current in their device was determined by either recombination current or tunneling current depending on the temperature. 16) Jensen et al examined n a-Si:H (12.5 nm)/p c-Si heterojunction solar cells and explained that the forward current of their device was dominated by the diffusion current in the c-Si region. 7) Because the a-Si:H layers in these experiments were very thin, the junction property seemed to be determined by the c-Si layer where the depletion zone mainly spreads.…”
Section: Transport Mechanismmentioning
confidence: 99%
“…In fact, all the implanted samples, as-implanted or annealed, show rectifying behaviors. Information on the transport mechanisms can be obtained from the temperature variation of the voltage derivative of the I-V characteristics [ 16,17]. Details of these analyses will be presented elsewhere [16,18].…”
Section: Resultsmentioning
confidence: 99%